Study of adsorption-based cooling and potable water generation - Tay, Xiu-Ling (2017)
In present day, global warming and climate change have become more apparent. The Kyoto Protocol increased pressure on governments to reduce the emission of greenhouse gases which contribute to global warming. One such group of gases are hydrofluorocarbons (HFCs) used as refrigerants in refrigeration systems. Additionally, a typical refrigeration system uses electricity that requires the burning of fossil fuels, to operate. Hence, there is greater global interest in exploring greener alternatives to alleviate the issue. Adsorption refrigeration system presents itself as a cleaner alternative to the typical refrigeration system as it utilizes waste heat instead of electricity as a power source. Moreover, environmentally friendly substances like silica gel-water pair are used as refrigerants.